Short-term effects of TAF 273 on oestrous cycle and reproductive hormones of normal rats - Ahmad, Nur Amalina; Abdul Rahman, Suzanah; Chan, Kit-Lam; Mamat, Suhana; Abdul Samat, Nadia Hanis; Abdullah, Afif Raihan; Mohd Zahri, Syazana (2015)
Eurycoma longifolia is one of the plants used to enhanced male reproductive functions but little is known for its effect on the female reproductive system and functions. Therefore this work is performed to study the effects of standardized extract of Eurycoma longifolia, TAF 273, on oestrous cycle and some reproductive functionality in rats. Female Sprague-dawley rats (7-8 weeks old) weighing between 160-230 g were used in this study. Vaginal smear of each rat was monitored daily for 2-week period (cover 3 cycles) in order to select females with normal cycle (4-5 days). Those with regular cycle were randomized into seven groups of 6 animals each. Rats in the treatment group received the extract orally at different doses (2.5, 5, 10, 25, 50 and 100 mg/kg body weight) for 5 days (one complete cycle) whereas the control group received an equal volume of distilled water in a similar manner. The oestrous cycle pattern of both control and treatment groups were monitored daily and recorded during the 5 days treatment and during the following 15 days after withdrawal of treatment. The body weight of the females was recorded before and after 5 days treatment. At the end of the experiments, blood samples were collected and the serum were analysed for oestrogen, progesterone and testosterone levels. Ovaries and uteri were removed, weighed and examined for histomorphological changes. The results showed that the administration of TAF 273 did not significantly alter the analyzed variables. Therefore, the data obtained indicate that Eurycoma longifolia standardized extract did not exhibit any detrimental effects on the oestrous cycle, ovarian histomorphology and female reproductive hormones.